2014
DOI: 10.1002/bab.1165
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrobiosis in yeast: FT‐IR spectroscopic studies of yeast grown under conditions of severe oxygen limitation

Abstract: Anhydrobiosis is a unique state of living organisms when metabolism is temporarily and reversibly delayed in response to the extreme desiccation of cells. The production of dry active preparations of yeast grown under anaerobic conditions is not currently possible because preparations are extremely sensitive to the dehydration procedure, though they could be very helpful in different biotechnological processes, including bioethanol production. To characterize mechanisms responsible for such sensitivity to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On the one hand, the loss of some molecular components may be related to the increase in the lipids content (Burattini et al, 2008). On the other hand, this higher concentration may be a result of the plasma membrane disorder and fluidity (Grube et al, 2014). These findings suggest that the resistance of L. thermotolerans yeast is accompanied by modifications in lipid profiles.…”
Section: Evolution Of Lipids Profiles Of Yeast L Thermotolerans Durimentioning
confidence: 96%
“…On the one hand, the loss of some molecular components may be related to the increase in the lipids content (Burattini et al, 2008). On the other hand, this higher concentration may be a result of the plasma membrane disorder and fluidity (Grube et al, 2014). These findings suggest that the resistance of L. thermotolerans yeast is accompanied by modifications in lipid profiles.…”
Section: Evolution Of Lipids Profiles Of Yeast L Thermotolerans Durimentioning
confidence: 96%
“…It was also revealed that some special procedures may increase the resistance of cells to desiccation stress. For example, the incubation of cells in solutions with increased osmotic pressure is very effective in increasing their resistance to desiccation stress [12][13][14][15][16]. The state of anhydrobiosis is now used widely in the successful long-term maintenance of yeast viability and the large-capacity production of active dry baker's yeast.…”
Section: Introductionmentioning
confidence: 99%